Improvement in Quality of Life in Patients with Moderate to Severe Psoriasis Treated with Adalimumab or Ustekinumab. Issue 4 (September 2016) - Nakamura, Mio; Zhu, Tian Hao; Abrouk, Michael; Farahnik, Benjamin; Singh, Rasnik; Lee, Kristina; Koo, John; Bhutani, Tina
Introduction: Quality of life (QoL) is an important issue in psoriatic disease that should be included when assessing therapeutic efficacy of treatments. The objective of this study was to compare improvement in the dermatology life quality index (DLQI) between patients treated with adalimumab and ustekinumab. Methods: Analysis was based on two separate open-label 24-week clinical trials assessing DLQI and the Psoriasis Area and Severity Index (PASI) at four-week intervals in adult subjects with moderate to severe psoriasis treated with adalimumab or ustekinumab. Results: There were no statistically significant differences in the improvement in DLQI and PASI between the adalimumab and ustekinumab groups except at week 12 for DLQI and week 8 for PASI (ustekinumab > adalimumab). Discussion: Both adalimumab and ustekinumab improve QoL, but further research is necessary to determine specific factors that improve QoL and if one medication improves QoL more than another.